Evaluation of a field test to assess aerobic endurance and performance in elite caclists - Nimmerichter, A.; Williams, C.; Eston, R. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
The assessment of endurance performance is usually conducted during laboratory ergometer tests. In field tests, time to complete a given distance is often the chosen performance measure. Since external conditions can largely influence these measures, the aim was to evaluate the reliability of power output in a field test and validate performance measures obtained from a traditional laboratory ergometer test. Methods: Fifteen competitive male cyclists (age: 25.6 ± 5.2 y; height: 180.6 ± 4.5 cm; weight: 70.6 ± 4.4 kg; VO2max: 67.1 ± 5.0 ml/min/kg) completed an incremental graded exercise test (GXT) to determine ventilatory threshold, respiratory compensation point (VT, RCP) and lactate turn points (LTP1, LTP2) and two maximal aerobic power 4-min (MAP 4) and 20-min (MAP 20) time-trials, during which power output was measured with mobile power cranks (SRM). Results: Power (W) was 263 ± 37, 344 ± 38, 243 ± 27, 344 ± 37 and 440 ± 38 W, for LTP1, LTP2, VT, RCP and Pmax, respectively. Average power during the 4-min time-trial (412 ± 53 W) was significantly higher (p < 0.001) than during the 20-min time-trial (347 ± 42 W) and was correlated with (r = 0.791 to 0.878, p < 0.001) but significantly different from (p < 0.001) performance markers obtained during GXT. No significant differences were observed between the 20-min time-trial, LTP2 (p = 0.946) and RCP (p = 0.853). Strong test-retest correlations for MAP 4 (ICC = 0.976, p < 0.001) and MAP 20 (ICC = 0.985, p < 0.001) were observed. Discussion: The test-retest reproducibility was in agreement with the results of a 40-km outdoor time-trial reported by Smith et al. (2001). The reliability of a 3-min laboratory all out test has been published by Burnley et al. (2006) where typical error was found to be ± 7 W or 3 %, which is similar to the results of the 4-min time-trial (± 8 W or 2.2 %). Measures of aerobic performance explained 65 % - 77 % of the variance in MAP 4 and MAP 20. The 4-min time-trial was on average 93 % of Pmax from GXT, reflecting the ability of high-level athletes to tolerate intensities of 95 % - 105 % over 4-15 min. Average power during 20-min time-trial was 79 % of Pmax, which is in accordance with exercise intensities during time-trials in professional cyclists (Lucia, et al., 2001). In conclusion the 4-min and 20-min time-trials are reliable measures of aerobic endurance. The 20-min time-trial is valid to predict RCP and LTP2.